back to the math tutorial index back to the math tutorial index

Differentiating Special Functions

In this tutorial, we review the differentiation of trigonometric, logarithmic, and exponential functions.

Trigonometric Functions

The derivatives of the basic trigonometric functions are given here for reference. \[\begin{array}{rr} f(x) & f'(x)\\ ~\\ \qquad\qquad\sin x & \cos x\\ \cos x & -\sin x\\ \tan x & \sec^2 x\\ \sec x & \sec x \tan x\\ \csc x & \qquad\qquad -\csc x\cot x\\ \cot x & -\csc^2 x\\ ~\\ \end{array}\] The derivatives of $\sin x$ and $\cos x$ can be derived using the limit definition of the derivative For $\sin x$, \begin{eqnarray*} \frac{d}{dx}(\sin x)&=&\lim_{h\to 0} \frac{\sin (x+h)-\sin (x)}{h}\\ &=& \lim_{h\to 0} \frac{(\sin x\cos h+\cos x\sin h)-\sin x}{h}\\ &=& \lim_{h\to 0} \left[\sin x\frac{\cos h -1}{h}+\cos x\frac{\sin h}{h}\right]\\ &=&\sin x\lim_{h\to 0}\left[\frac{\cos h-1}{h}\right]+\cos x\lim_{h\to 0}\left[\frac{\sin h}{h}\right]\\ &=& \sin x (0)+\cos x (1)\\ &=& \cos x. \end{eqnarray*} The derivative of $\cos x$ is derived analogously. Then the remaining derivatives can be derived using the quotient rule, since all the other trigonometric functions are quotients involving $\sin x$ and $\cos x$.

Example

The derivative of $\tan (x^2)$ is $\displaystyle \sec^2(x^2)\cdot\frac{d}{dx}(x^2) =2x\sec^2(x^2)$ by the chain rule.

Logarithmic Functions

By the definition of the natural logarithm, $\displaystyle \frac{d}{dx}[\ln x] =\frac{1}{x}$ for $x>0$. Also, $\displaystyle \frac{d}{dx} [\ln |x|]=\frac{1}{x}$ for all $x\neq 0$. To see this, suppose $x<0$. Then $\ln |x|=\ln (-x)$.

So \begin{eqnarray*} \frac{d}{dx}[\ln |x|]&=&\frac{d}{dx}[\ln (-x)]\\ &=& \frac{d}{dx}(-x)\left(\frac{1}{-x}\right)\\ &=& (-1)\left(\frac{1}{-x}\right)\\ &=& \frac{1}{x}. \end{eqnarray*}

Example

By the chain rule, the derivative of $\ln (x^3+5)$ is $\displaystyle \frac{d(x^3+5)}{dx}\cdot\frac{1}{x^3+5}=\frac{3x^2}{x^3+5}$.

Exponential Functions

There is an elegant way to show that $\displaystyle \frac{d}{dx}\left[e^x\right]=e^x$. We start with the identity $\displaystyle \ln (e^x)=x$. Differentiating both sides, \begin{eqnarray*} \frac{d}{dx}[\ln (e^x)]&=&\frac{d}{dx}(x)\\ \frac{d}{dx}[\ln (e^x)]&=& 1\\ \frac{d}{dx}(e^x)\cdot \frac{1}{e^x}&=&1\\ \frac{d}{dx}(e^x)&=&e^x. \end{eqnarray*} Since $e^x$ is never $0$, this derivation holds for all $x$.

Example

The derivative of $\displaystyle e^{-3x+2}$ is $\displaystyle e^{-3x+2}\cdot \frac{d}{dx}(-3x+2)=-3e^{-3x+2}$.


Key Concepts

\[\begin{array}{rr} f(x) & f'(x)\\ ~\\ \qquad\qquad\sin x & \cos x\\ \cos x & -\sin x\\ \tan x & \sec^2 x\\ \sec x & \sec x \tan x\\ \csc x & \qquad\qquad -\csc x\cot x\\ \cot x & -\csc^2 x\\ \ln x & \frac{1}{x}\\ e^x & e^x\\ ~\\ \end{array}\]